Selected Spatiotemporal and Joint Angle Parameters in Normal Gait and Nordic Walking with Classical and Mechatronic Poles in Aspects of Sex Differences. (13th December 2022) - Szpala, Agnieszka; Kołodziej, Małgorzata; Struzik, Artur; Jasiński, Ryszard; Bałchanowski, Krzysztof J.; Pietraszewski, Bogdan; Woźniewski, Marek
Abstract : Introduction. The aim of this study was to compare selected spatiotemporal parameters and changes in the range of motion in the joints of lower and upper limbs during normal gait and during Nordic walking performed with classical and mechatronic poles of females and males. Methods . The study involved 19 physical education students (11 males and 8 females). The MyoMotion research motion analysis system was used to collect gait kinematic variables. The subject task was to cover a 100 m distance in a straight line with three types of gait: gait without poles, gait with classical poles, and gait with mechatronic poles at preferred velocity. Parameters were measured both on the right (RT) and on the left side (LT) of the body. The data was analyzed using two-way repeated measures ANOVA with the between-subject factor "sex." Friedman's test was used when necessary. Results . The most significant differences in spatiotemporal parameters between males and females were revealed in gait with the classical and mechatronic pole (stance phase LT and RT, load response LT and RT, single support LT and RT, preswing LT and RT, swing phase LT and RT, double stance LT and RT, and step length LT), the least in gait without a pole (stance phase RT, load response LT, single support LT, preswing RT, and swing phase RT); whereas, the most significant differences in kinematic parameters were revealed in gait without poles (shoulder rotation RT, wrist radial-ulnar LT, hip flexion-extension LT and RT, knee flexion-extension LT and RT, ankle inversion-eversion LT, and ankle abduction-adduction LT and RT), the least in gait with mechatronic poles (knee flexion-extension LT and RT, ankle dorsiflexion-plantarflexion LT, ankle inversion-eversion LT, and ankle abduction-adduction LT and RT). Conclusion . Statistical analysis revealed many differences in spatiotemporal and kinematic parameters in normal gait, as well as in gait with the classical and mechatronic poles, which allows the conclusion that the gait of females and males should be analyzed separately.